Tumor Suppressor Par-4 Regulates Complement Factor C3 and Obesity - Araujo, Nathalia; Sledziona, James; Noothi, Sunil K.; Burikhanov, Ravshan; Hebbar, Nikhil; Ganguly, Saptadwipa; Shrestha-Bhattarai, Tripti; Zhu, Beibei; Katz, Wendy S.; Zhang, Yi; Taylor, Barry S.; Liu, Jinze; et al. (Frontiers in Oncology, 2022)
Prostate apoptosis response-4 (Par-4) is a tumor suppressor that induces apoptosis in cancer cells. However, the physiological function of Par-4 remains unknown. Here we show that conventional Par-4 knockout (Par-4-/-) mice and adipocyte-specific Par-4 knockout (AKO) mice, but not hepatocyte-specific Par-4 knockout mice, are obese with standard chow diet. Par-4-/- and AKO mice exhibit increased absorption and storage of fat in adipocytes. Mechanistically, Par-4 loss is associated with mdm2 downregulation and activation of p53. We identified complement factor c3 as a p53-regulated gene linked to fat storage in adipocytes. Par-4 re-expression in adipocytes or c3 deletion reversed the obese mouse phenotype. Moreover, obese human subjects showed lower expression of Par-4 relative to lean subjects, and in longitudinal studies, low baseline Par-4 levels denoted an increased risk of developing obesity later in life. These findings indicate that Par-4 suppresses p53 and its target c3 to regulate obesity.